Online Web-Based Learning and Assessment Tool in Vocational High School for Physics - Gita Ayu Permatasari; Ellianawati Ellianawati; Wahyu Hardyanto (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
ICT has transformed the conventional learning system into a modern learning system, demanding innovation in the delivery of learning. So that this study has the aim of developing, knowing the feasibility of online web-based learning and assessment tool in physics, as well as knowing students' learning results in the ICT media. This study research & development (R&D) method using Borg & Gall model. Which refers to the potential problem through data collection, product design, design validation, revision of product design, product testing, revision of usage. The feasibility testing of media and material was carried out by two material expert validators and two media expert validators with a small group trial conducted on students consisting of 13 respondents and large group trial conducted on students consisting of 40 respondents. We use online media for web-based learning and assessment tool in vocational high school for Physics subject, and the results of the study show that this application generates individual assignments, marks student responses, supplies students with the rapid feedback, and records student activities. The student activity log provides insight into student learning habits. Its a reference for assessment. This application meets the requirements as a learning media. The results of the validation by an expert material on online web-based learning and assessment tool gets a percentage of an average score of 82%, and the material gets a percentage of 81.33% criteria very feasible.